Microbial and Heavy Metal Contaminant of Antidiabetic Herbal Preparations Formulated in Bangladesh. (26th October 2015) - Zamir, Rausan; Hosen, Anowar; Ullah, M. Obayed; Nahar, Nilufar
Abstract : The aim of the current study was to evaluate microbial contamination in terms of microbial load (total aerobic count and total coliform count) and specific pathogenic bacteria ( Salmonella spp., Escherichia coli, particularly Escherichia coli 0157) in thirteen antidiabetic herbal preparations (ADHPs) from Dhaka City. All the thirteen ADHPs had been found contaminated with fungi and different pathogenic bacteria. From the data, it is found that only two of these preparations (ADHP-1 and ADHP-12) complied with the safety limit (as stated in different Pharmacopoeias and WHO guidelines) evaluated by all different microbial counts. None of these herbal preparations could assure the safety as all of them were contaminated by fungi. The overall safety regarding heavy metal content (Zn, Cu, Mn, Cr, Cd, and Pb) was assured as none of them exceeded the safety limit of the daily intake. Microbial contaminants in these herbal preparations pose a potential risk for human health and care should be taken in every step involved in the preparation of these herbal preparations to assure safety.